2019
DOI: 10.1021/acs.jpcc.9b08460
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Responses of ZIF-8 under High Pressure: A Combined Raman and X-ray Diffraction Investigation

Abstract: ZIF-8 is a prototypical porous material in the family of zeolitic imidazolate frameworks, and its structural stability is of great significance for a wide range of practical applications. Here, the intrinsic and extrinsic structural and mechanical responses of nanosized ZIF-8 perturbed by high external pressure have been comparatively investigated based on our in situ Raman measurements in different pressure environments, accompanied by synchrotron X-ray diffraction measurements and results from previous repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 86 publications
2
30
0
Order By: Relevance
“…We have demonstrated that the pressure‐induced total amorphization of ZIF‐8 in liquid nitrogen is postponed to a much higher pressure of 28 GPa, and most Raman bands of ZIF‐8 move to higher wavenumber with respect to those in alcohols and water in the combined Raman and XRD study on ZIF‐8. [ 35 ] These results suggest that the framework is in a strained state at all time as pressure increases, withstanding not only a strong supporting/squeezing effect from the inner nitrogen molecules but also a highly external compression applied by the pressure transmitting medium. The host framework and the guest molecules interact on each other mutually in the confinement systems.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…We have demonstrated that the pressure‐induced total amorphization of ZIF‐8 in liquid nitrogen is postponed to a much higher pressure of 28 GPa, and most Raman bands of ZIF‐8 move to higher wavenumber with respect to those in alcohols and water in the combined Raman and XRD study on ZIF‐8. [ 35 ] These results suggest that the framework is in a strained state at all time as pressure increases, withstanding not only a strong supporting/squeezing effect from the inner nitrogen molecules but also a highly external compression applied by the pressure transmitting medium. The host framework and the guest molecules interact on each other mutually in the confinement systems.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that the structure of ZIF‐8 transforms to a high‐pressure phase above 1 GPa, due to reorientation of the methyl imidazolate ring triggered by interactions from the guest molecules. [ 35,38 ] This new structure exhibits enlarged diameters of the 4MR and 6MR windows and can capture more guests (see Figure 2). Our recent study showed that ZIF‐8 behaved in different ways in the presence of nitrogen molecules as pressure‐transmitting medium (PTM) in comparison with those obtained when nonpenetrating silicone oil was used or no PTM was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZIF-8 showed a characteristic band at 176 cm À1 and weak band at 281 cm À1 , originated from the Zn-N vibrations in the ZnN 4 tetrahedrons. 35,36 The high-frequency bands at 686 cm À1 , 1148 cm À1 , and 1460 cm À1 were attributed to imidazolate ring puckering, C-N stretching and C-H bending in the methyl group, respectively.…”
Section: Resultsmentioning
confidence: 99%